If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1(7 + -4x) = 9 1 + (7 * -1 + -4x * -1) = 9 1 + (-7 + 4x) = 9 Combine like terms: 1 + -7 = -6 -6 + 4x = 9 Solving -6 + 4x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 4x = 9 + 6 Combine like terms: -6 + 6 = 0 0 + 4x = 9 + 6 4x = 9 + 6 Combine like terms: 9 + 6 = 15 4x = 15 Divide each side by '4'. x = 3.75 Simplifying x = 3.75
| -2x-4=-9x+3 | | 15=5x-6+6 | | 7x-3y+31-5=3x | | 1.25+c=22.50 | | 71cmusen=3.14 | | 10x-1=5x-21 | | 4ln(x)+3y^2-1=3ln(x)+2y^2+1 | | -5(6v-8)-2=-4(1-3v) | | 1.5x+(1-x)=1.126 | | Z=7(x-h) | | 6w=150 | | 7x+(-5y)+(-9x)+19y= | | 9u-18=3u+12 | | y=(s^2+31.5s+250)(0.0025s^2+0.05s+1) | | 4g=(4g)(x) | | 20*x+100*y=1000 | | 9x-4+18x-2=8x+10 | | Y=2y-5 | | 20.5k=82 | | 22-8=(-2)+v(-7) | | Y=-3sen(2x)/x^2 | | 8(x+2)+8x=2(8x+6) | | 8n=108 | | 3.8+x=0.6 | | -1(x+4)= | | 6.37+4.2c=7.4c+8.95 | | 8x+3=-53 | | -8a+(-15a)= | | 2x+8(9x+6)=48 | | (6x^2+7x-9)-(8x^2-4x+7)= | | (45x^2+36x^3)= | | 4x-2x+5=21 |